Optimization of cleaning process parameters to remove abrasive particles in post-Cu CMP cleaning *Project supported by the Major National Science and Technology Special Projects (No. 2016ZX02301003-004-007), the Natural Science Foundation of China (No. 61704046), the Scientific Innovation Grant for Excellent Young Scientists of Hebei University of Technology (No. 2015007), and the Hebei Natural Science Foundation Project (No. F2018202174). (December 2018) - Yang, Liu; Tan, Baimei; Liu, Yuling; Gao, Baohong; Han, Chunyu
Abstract: The cleaning of copper interconnect chemical mechanical polishing (CMP) is a key process in integrated circuits (ICs) fabrication. Colloidal silica, which is used as the abrasive material in copper CMP slurry, is considered as the main particle contamination. Abrasive particle residuals can cause device failure which need to be removed efficiently. In this paper, a type of CMP cleaner was used for particle removal using a cleaning solution consisting of FA/O II chelating agent and FA/O I surfactant. By varying the parameters of brush rotation speed, brush gap, and de-ionized water (DIW) flow rate, a series of experiments were performed to determine the best cleaning results. Atomic force microscope (AFM) measurement was used to characterise the surface morphology of the copper surface and the removal of abrasive particles. A scanning electron microscope (SEM) with EDX was used to observe and analyze the particles shape and elements. The optima parameters of CMP cleaner were obtained. Under those conditions, the abrasive silica particles were removed effectively.